From Cognitive to Meta-cognitive Strategies: Integration of Grammar Learning in MALL Environment - Nadia, Refat; Hafizoah, Kassim (Universiti Malaysia Pahang, 2016)
Cognitive learning refers to the process or operation used for learning that requires direct synthesis of learning materials. On the other hand, metacognitive learning involves thinking of the learning process. The first approach of learning is cognitive understanding while the metacognitive entails the options of enhancing the understanding of the learning progress. In a technology enhanced environment, more specifically using mobile devices for learning, helps further to accelerate the both process of learning. It is observed through empirical studies that language learning can be improved through using cognitive and metacognitive strategies. Grammar as a crucial part of language learning is also taking a noticeably important part where learning process is mixed from cognitive to metacognitive steps. In using mobile for grammar learning, learner first infer or guess the task from the context through mobile and elaborate it from the previous experience or relate it to new experience to the other concept of memory. It is learners’ cognitive ability that he or she is applying for learning, while using different applications, web searches are working as metacognitive strategies to improve the learning. Previous studies either focused the traditional approaches or computer assisted language learning but in modern era where mobile is used widely, it is noteworthy to take initiate for facilitating grammar learning through cognitive and metacognitive strategies. This should be integrated by following well-designed instructions and proper modelling of grammar learning strategies.